PENERAPAN PSAK NO.109 DALAM PENYUSUNAN LAPORAN KEUANGAN ORGANISASI PENGELOLA ZAKAT DI KABUPATEN CIREBON (Studi Kasus Pada Kantor Baznas di Kabupaten Cirebon) - Isrin Hikmayanti; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine how the application of the financial statements of zakat management organizations at BAZNAS Cirebon district, to determine the suitability of the application of recognition, measurement, presentation and disclosure of PSAK Syariah No.109 at BAZNAS Cirebon district. The object and location of this research is in BAZNAS Cirebon Regency. The operational definition of the variables used in this study as zakat accounting information and can be used as a tool to measure the performance of the BAZNAS Management Institution. This can be measured from the way of recognition, distribution, measurement and presentation in PSAK 109. The sources used are primary data, namely data sources that directly provide data for data collection and secondary data in the form of BAZNAS Annual Reports, financial reports and other supporting data. needed in this research. This type of research uses analytical descriptive methods. Data collection techniques use literature studies, interviews, and documentation. The results of this study indicate that the recognition and distribution of zakat funds are not in accordance with PSAK No.109. In terms of the presentation of the zakat fund report, it is appropriate in the application of zakat accounting based on PSAK No. 109. disclosure of zakat funds is still not in accordance with zakat accounting standards because in asset management there is no input and recording. Keywords: Application of PSAK No. 109, Financial reports, Zakat Management Organization.